Holocene Hydroclimate Variability and Vegetation Response in the Ethiopian Highlands (Lake Dendi) - Jaeschke, Andrea; Thienemann, Matthias; Schefuß, Enno; Urban, Jonas; Schäbitz, Frank; Wagner, Bernd; Rethemeyer, Janet (Frontiers in Earth Science, 2020)
Northern Africa’s past climate is characterized by a prolonged humid period known as the African Humid Period (AHP), giving origin to the “Green Sahara” and supporting human settlements into areas that are now desert. The spatial and temporal extent of climate change associated with the AHP is, however, subject to ongoing debate. Uncertainties arise from the complex nature of African climate, which is controlled by the strength and interactions of different monsoonal systems, resulting in meridional shifts in rainfall belts and zonal movements of the Congo Air Boundary (CAB). Here, we examine a ~12,500-year record of hydroclimate variability from Lake Dendi located in the Ethiopian highlands based on a combination of plant‐wax‐specific hydrogen (δD) and carbon (δ13C) isotopes. In addition, pollen data from the same sediment core are used to investigate the response of the regional vegetation to changing climate. Our δD record indicates high precipitation during peak AHP (ca. 10 to 8 ka BP) followed by a gradual transition towards a drier late Holocene climate. Likewise, vegetation cover changed from predominant grassland towards an arid montane forest dominated by Juniperus and Podocarpus accompanied by a general reduction of understory grasses. This trend is corroborated by δ13C values pointing to an increased contribution of C3 plants during the mid‐ to late Holocene. Peak aridity occurred around 2 ka BP, followed by a return to a generally wetter climate possibly linked to enhanced Indian Ocean Monsoon strength. During the last millennium, increased anthropogenic activity, i.e. deforestation and agriculture is indicated by the pollen data, in agreement with intensified human impact recorded for the region. The magnitude of δD change (40‰) between peak wet conditions and late Holocene aridity is in line with other regional δD records of East Africa influenced by the CAB. The timing and pace of aridification parallels those of African and Indian monsoon records indicating a gradual response to local insolation change. Our new record combining plant‐wax δD and δ13C values with pollen highlights the sensitive responses of the regional vegetation to precipitation changes in the Ethiopian highlands.